Handbook on adolescent and adult immunization - Parthasarathy, A.; Gupta, Alok (Jaypee Brothers Medical Publishers (P) Ltd, 2014)
The practicing pediatricians and family physicians need to concentrate to provide these vaccines to their adolescent and adult clients. With the objective of providing the needed information in concise manner, the contents of this book have been designed to help practitioners in their office practice